SUSTAINABLE HETEROGENEITY IN EXOGENOUS GROWTH MODELS. THE SOCIALLY OPTIMAL DISTRIBUTION BY GOVERNMENT’S INTERVENTION - HARASHIMA, Taiji (Theoretical and Practical Research in Economic Fields; Vol 5 No 1 (2014): TPREF, Volume V, Issue 1(9), Summer 2014DO - 10.14505/tpref.v4.2(8).07, 2014)
This paper examines the socially optimal allocation by focusing not on the social welfare function but instead on the utility possibility frontier in exogenous growth models with a heterogeneous population. A unique balanced growth path was found on which all of the optimality conditions of all heterogeneous households are equally and indefinitely satisfied (sustainable heterogeneity). With appropriate government interventions, such a path is always achievable and is uniquely socially optimal for almost all generally usable (i.e., preferences are complete, transitive, and continuous) social welfare functions. The only exceptions are some variants in Nietzsche type social welfare functions, but those types of welfare functions will rarely be adopted in democratic societies. This result indicates that it is no longer necessary to specify the shape of the social welfare function to determine the socially optimal growth path in a heterogeneous population.